Impact of estrogen replacement on growth, skeletal maturation, bone density and body composition in a girl with novel aromatase gene mutation - Agarwal, Neha; Shukla, Rishi; Bajpai, Anurag (International Journal of Contemporary Pediatrics, 2021)
Aromatase deficiency is a rare autosomal recessive disorder characterized by impaired androgen to estrogen conversion. We report a 13.5-year-old girl initially misdiagnosed as simple virilising 21 hydroxylase deficiency who presented with delayed puberty. Work-up showed aromatase deficiency due to novel mutation in the aromatase gene. Estradiol replacement was associated with increased growth, skeletal maturation, bone density and adiposity. Early estrogen treatment in our case may have prevented metabolic complications and ovarian cysts.